2016
DOI: 10.1007/s00038-015-0783-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of electronic nicotine delivery systems and recent initiation of smoking among US youth

Abstract: Use of ENDS by adolescents was associated with initiation of cigarette smoking in the last year. This association was stronger in younger adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…38 Recent media reports linking e-cigarettes and e-liquid to serious injuries, 39,40 exposure to toxicants, 41 development of lung diseases, 42 and other health related problems 43 may have contributed to the increasing trend of equating the harm of e-cigarettes to traditional cigarettes. Lastly, U.S. adults may be partially equating the harm of e-cigarettes to combustible cigarettes owing to other concerns related to the potential of e-juice flavors to lure children into addiction, 44,45 the use of e-cigarettes with illicit drugs, 46 and the concern that their use could renormalize smoking. 47 Future research should examine the role of such issues in shaping individual perceptions about e-cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…38 Recent media reports linking e-cigarettes and e-liquid to serious injuries, 39,40 exposure to toxicants, 41 development of lung diseases, 42 and other health related problems 43 may have contributed to the increasing trend of equating the harm of e-cigarettes to traditional cigarettes. Lastly, U.S. adults may be partially equating the harm of e-cigarettes to combustible cigarettes owing to other concerns related to the potential of e-juice flavors to lure children into addiction, 44,45 the use of e-cigarettes with illicit drugs, 46 and the concern that their use could renormalize smoking. 47 Future research should examine the role of such issues in shaping individual perceptions about e-cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…Several mostly cross-sectional studies found higher susceptibility to trying cigarettes among adolescent or young adult ECIG users who had never smoked cigarettes [235,[254][255][256][257][258], while others found tobacco use to be a predictor of intention to use ECIGs [259,260]. Several cross-sectional studies found an association between ECIG use and smoking [260][261][262][263][264][265][266]. One study suggested that ECIG use leads to tobacco smoking [261], while others indicate that tobacco use is a risk factor for ECIG use [260,262,263,266].…”
Section: Does Ecig Use Deter Smoking Cessation?mentioning
confidence: 99%
“…In some cross-sectional studies, ever e-cig users had higher odds for having smoking intention8 and openness to cigarette smoking than never users 9 . Trying e-cigs was a significant predictor of future cigarette smoking in many studies [10][11][12][13][14] . However, some studies using UK data reported that regular use of e-cigs is almost entirely concentrated in adolescents who already smoke and are not progressing to habitual use 15,16 .…”
Section: Introductionmentioning
confidence: 99%